HYBRIDITY AND UNHOMELINESS IN FADIA FAQIR'S WILLOW TREES DON'T WEEP: ANALYTICAL STUDY IN POSTCOLONIAL DISCOURSE - Fazel Asadi Amjad, Sarmad Albusalih (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The present study is an attempt to shed light on Fadia Faqir's Willow Trees Don't Weep (2014) with a reference to Homi Bhabha's hybridity and unhomeliness. The critical analysis of the novel reveals that Najwa, Faqir's protagonist, acquiesces to practice hybridity and unhomeliness in Willow Trees Don't Weep. Faqir's other characters push Najwa to their own favored kind of identity and Najwa is caught in a state of hybridity and unhomeliness. She is upset by the heaviness of dualism between the Western and the Islamic worlds. It might be argued that the choice of Najwa's father, Omer Rahman, of Jihad and also her mother's secular thoughts and ideas considerably aggravated Najwa’s state of life toward a fragmented state of identity. Najwa’s research journey for finding her father, who abandoned his family since she was three years old. After she reached twenty-seven years of age and shortly after her mother’s death it becomes imperative for her to find him because of the harshness of the Jordanian society which traditionally considers a house without a man is a house without honor. The Jordanian patriarchy society instigates Najwa to undertake the journey and during the journey, Najwa undergoes the experience of cultural hybridity and unhomely feeling.